Role of Sirtuins in Tumor Angiogenesis - Edatt, Lincy; Poyyakkara, Aswini; Raji, Grace R.; Ramachandran, Vishnu; Shankar, S. Sharath; Kumar, V. B. Sameer (Frontiers in Oncology, 2020)
Changes in the metabolic status of cells under conditions like hypoxia and accumulation of lactate can be sensed by various sensing mechanisms which leads into modulation of number of signal transduction pathways and transcription factors. Tumors under hypoxic microenvironment secretes a number of proangiogenic cytokines like VEGF, FGF, PDGF, TGF-β, Ang-2, ILs etc. These cytokines binds to their receptors on the endothelial cells and activates a number of signalling pathways including Akt/PIP3, Src, p38/MAPK, Smad2/3 etc. which ultimately results in the proliferation and migration of endothelial cells. Transcription factors that are activated under the metabolic status of tumors include HIF, NF-κb, p53, El-2 and FOXO. Many of these transcription factors has been reported to be regulated by a class of histone deacetylase called Sirtuins. Sirtuins are NAD+ dependent histone deacetylases that play pivotal role in the regulation of tumor cell metabolism, proliferation, migration and angiogenesis. The major function of Sirtuins are deacetylation of histones and non-histone proteins like NF-κB, FOXOs, PPARϒ, PGC1-α, enzymes like acetyl coenzymeA and structural proteins like α tubulin. Sirtuins are generally considered as the redox sensors in the cell and their activities are dependent on the metabolic status of the cell. Understanding the intricate mechanisms of regulation adopted by Sirtuins is important to device effective therapeutic strategies against angiogenesis, metastasis and tumor progression. Keeping this in mind, the present review discusses the role of Sirtuins in the process of tumor angiogenesis and the regulatory mechanisms employed by them in detail.